2012
DOI: 10.1556/eujmi.2.2012.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of enzymatic tissue disintegration on the level of surface molecule expression and immune cell function

Abstract: Immunological characterization of immune cells that reside in specific anatomic compartments often requires their isolation from the respective tissue on the basis of enzymatic tissue disintegration. Applying enzymatic digestion of primary splenocytes, we evaluated the impact of collagenase and dispase, two enzymes that are commonly used for the liberation of immune cells from tissues, on the detectability of 48 immunologically relevant surface molecules that are frequently used for flow cytometric identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
116
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 21 publications
(26 reference statements)
11
116
0
Order By: Relevance
“…We therefore investigated the effect of in vivo miR-155 inhibition on the expression of several M/M phenotypic markers, at different time points after dMCAO. We used immunofluorescence staining and Western blot for these experiments, since brain tissue disintegration (both without and with fixation) affects detectability of cell surface markers and, thus, accuracy of FACS-based analysis [46]. Immunofluorescence staining of the histological sections did not show visible differences in CD206 (C-type lectin mainly present on the surface of macrophages and immature dendritic cells) expression between inhibitor and control groups, at any examined time point after dMCAO (Additional file 1).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore investigated the effect of in vivo miR-155 inhibition on the expression of several M/M phenotypic markers, at different time points after dMCAO. We used immunofluorescence staining and Western blot for these experiments, since brain tissue disintegration (both without and with fixation) affects detectability of cell surface markers and, thus, accuracy of FACS-based analysis [46]. Immunofluorescence staining of the histological sections did not show visible differences in CD206 (C-type lectin mainly present on the surface of macrophages and immature dendritic cells) expression between inhibitor and control groups, at any examined time point after dMCAO (Additional file 1).…”
Section: Resultsmentioning
confidence: 99%
“…While tissue digestion with dispase had significant effects on many cell surface molecules, multiple rounds of low concentration of collagenase have been shown by others to have minimal effects on CD4 (22, 23). In regards to CCR7 expression, we showed that total cytobrush-derived CD4+ and CD8+ T cells from 3 participants isolated in the absence of collagenase also contained higher proportions of T EM (Supplemental Figure 1A), similar to what was observed in the biopsy samples (Fig.1).…”
Section: Discussionmentioning
confidence: 98%
“…An example of this is reported in Fig. 12.4; CD8 is rapidly lost on the surface of splenocytes and T cells from mouse mammary tumors if high concentrations of enzymes are used [40]. …”
Section: 2 Protocol For Isolation Of Resident Macrophages and Tamsmentioning
confidence: 99%
“…A number of different digestion methods exist that involve different incubation periods, agitation speeds, and enzymes [3537], but no protocol so far has been optimized for primary macrophage isolation. Moreover some digestion methods can result in loss of cell surface markers [3840]; therefore we have developed a protocol where the cell surface markers remain intact. In this chapter we review the FACS methods developed in our laboratory over the last few years for isolation and analysis of macrophages and TAMs from mouse and human normal mammary tissue and breast tumors.…”
Section: 1 Introductionmentioning
confidence: 99%